Moral Obligation and Punishment Alert: An Empirical Study of Accounting Undergraduate Behavior When Personal Interest Is Involved - Mohd Rizuan, Abdul Kadir; Amanuddin, Shamsuddin; Juwahir, Kayan; Rashidi, Abbas (Universiti Malaysia Pahang, 2017)
As a result too many major accounting failures, critics of accounting are likely to interpret this failure as a clear signal of the inability of the profession to maintain their discipline. An extensive research investigating ethical behaviour among practicing and prospective accountants and auditors has been made. This includes studies on accounting undergraduate as it is necessary to ensure they are on the right track to meet the business world. The purpose of this study is to investigate the effect of three variables, desire of outcome, punishment alert and moral obligation, on ethical decision making. We gave four scenarios to the students and asked them to rank the significance of the variables to their decision. Primary data were collected by self-administrated questionnaire involving a sample of 110 undergraduate accounting students’. From the result, we found that desired of outcome and moral obligation played significant role in explaining ethical decision making.